A rare Pluteus from Western Ghats of Kerala - Pradeep, C K; Vrinda, K B; Varghese, Shibu P (Mushroom Research, 2012)
During our study on the agaricoid basidiomycetes of Wayanad district of Kerala, a rare, remarkable Pluteus, known only from the type was collected. Detailed macro and microscopic examination revealed that it was Pluteus brunneopictus, so far known only from the type collected from Sri Lanka (Pegler, 1986) a century back.Â  The species is described, illustrated and discussed based on fresh collections made from Wayanad district of Kerala. Conventional morphology based taxonomic methods were employed for this study.Â  Colour notations refer to Kornerup & Wanscher (1978). All collections examined are deposited in the Mycological herbarium of TBGRI (TBGT).